Multi-proxy analyses of sediment core OCE2022-KV02-GC - Devendra, Dhanushka; Łącka, Magdalena; Szymańska, Natalia; Nethupul, Hasitha; Pawłowska, Joanna; Szymczak- Zyła, Małgorzata; Krajewska, Magdalena; De Silva, Prasadi; Bondevik, Stein; Gibbons, Steven J (PANGAEA, 2025)
We present a multi-proxy dataset from sediment core OCE2022-KV02-GC, retrieved from the northwestern Barents Sea (74°50.296′N, 16°1.3403′E; 374 m water depth) during the AREX 2022 expedition aboard RV Oceania. The dataset includes oxygen stable isotopes (measured primarily on Elphidium clavatum), total organic carbon (TOC), grain size, X-ray fluorescence (XRF) data, biomarkers (alkenones and sterols), terrestrial DNA, and magnetic susceptibility. All proxy data are presented relative to core depth.
Keywords: Barents Sea; sedaDNA; Sedimentology; simulation; Storegga Slide Tsunami; terrestrial biomarkers